Peningkatan Akurasi Skrining Disfagia Fase Faringeal Menggunakan Ultrasonografi pada Pasien Stroke Iskemik Akut: Sebuah Studi Kasus - Hidayati, Evi Rachmawati Nur; Yusviani, Hafizia Asri; Solecha, Dewi Listiani (Majalah Kedokteran Indonesia, 2023)
Introduction: Dysphagia is a common complication in acute stroke patients that require early screening to reduce the risk of aspiration pneumonia, disability, and mortality. Bedside examinations such as the Gugging Swallowing Screen (GUSS) test and ultrasonography are non-invasive methods that may improve early diagnosis of dysphagia after stroke. Case Report: We report a 49-year-old man with a history of cerebrovascular event that had difficulty swallowing, followed by coughing and choking after drinking. Discussion Case: The GUSS score indicated moderate dysphagia with a high risk of aspiration. The swallowing ultrasonography showed conformity to the GUSS score and improved the screening accuracy for silent aspiration risk in the pharyngeal swallowing phase. Conclusion: In conclusion, ultrasonography examination may improve the screening accuracy of the GUSS test, particularly for the detection of silent aspiration in pharyngeal dysphagia.